A case report of cryptococcal meningitis associated with ruxolitinib. Issue 13 (March 2020) - Tsukui, Daisuke; Fujita, Hiroaki; Suzuki, Keisuke; Hirata, Koichi
Abstract : Abstract: We herein report a 76-year-old Japanese man with myelofibrosis who developed cryptococcal meningitis. After treatment for 5 months with ruxolitinib, the patient presented with fever and disturbance of consciousness. Marked nuchal stiffness was noted. The magnetic resonance imaging results of the brain were normal. Lumbar puncture showed an opening cerebrospinal fluid (CSF) pressure of 110 mm H2 O, pleocytosis (85 mononuclear cells and 222 polymorphonuclear cells/μL), decreased CSF/serum glucose ratio (43%), and elevated protein (194 mg/dL). Blood and CSF cultures grew no bacteria or fungi. However, cryptococcal antigen was detected in the blood and CSF samples. We discontinued ruxolitinib and started administration of amphotericin B. His condition improved gradually 1 week after initiation of treatment. There have been only a few reports on cryptococcal meningitis associated with ruxolitinib. Physicians should consider the possibility of cryptococcal meningitis in patients receiving ruxolitinib.